A transition program from pictures communication symbols-augmented to authentic reading materials for children with autism - Reyes, Grace Lucila Angela Roman (2007)
This study sought to investigate whether children diagnosed with autism can have transition from reading Picture Communication symbols-augmented text to authentic reading materials. Using single case experiments, reversal design, four children underwent five controlled replications throughout the program. Intervention was applied over a 3-week period within a 15-day program, consisting of daily 30-minute sessions, 5 days a week. The entire program constituted a 7 1/2 hour cumulative session. Using cross-sectional data and qualittative analysis of findings, the study demonstrated significant positive improvement in reading accuracy of children with autism. The study suggested further areas for research in order to extend generalizability of this teaching methodology.
"April 2007."
Thesis (M.A. Reading Education)--University of the Philippines, Diliman.
Keywords: Autistic children -- Education -- Philippines -- Quezon City; Reading (Elementary) -- Philippines -- Quezon City; Teaching -- Philippines -- Quezon City -- Aids and devices; Picture books for children